Magnetic materials, iron cores and rotating electrical machines
By introducing nitrogen defects into the iron nitride α″-Fe16N2 and adjusting the molar ratio of iron and nitrogen, the problem of difficulty in obtaining high saturated magnetic beam density and low iron loss without increasing costs is solved in the prior art, and a more efficient magnetic material performance is achieved.
Patent Information
- Application Number
- JP2021073529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-23
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2041-04-23
AI Technical Summary
The prior art is difficult to obtain soft magnetic materials with high saturation magnetic beam density and low iron loss without increasing costs, especially in applications such as rotary electric machines and transformers.
By introducing nitrogen defects into the iron nitride α″-Fe16N2, the molar ratio of iron to nitrogen in its crystal structure is adjusted to exceed the ratio of 8:1, thereby increasing the saturated magnetic beam density of the magnetic material.
It realizes that the saturated magnetic beam density of magnetic materials in applications such as rotary motors and transformers is improved while maintaining low costs and reduces iron losses.
Smart Images

Figure 0007669180000002 
Figure 0007669180000003 
Figure 0007669180000004
Abstract
Description
[Technical field]
[0001] The present invention relates to α″-Fe 16 This paper relates to an iron nitride-based magnetic material based on N2, and to an iron core and a rotating electrical machine using the same.
[0002] Iron-cobalt alloys are known as alloys that exhibit a higher saturation magnetic flux density Bs than pure iron. The Bs of pure iron is 2.14 T at 20°C. For example, permendur Fe-49Co-2V has a bulk Bs of 2.3 T and is widely used in motor cores as a soft magnetic material with a high Bs. However, iron-cobalt alloys contain cobalt, which is more expensive than iron, and therefore have issues with mass production and cost.
[0003] In recent years, iron nitride α″-Fe has been used as a magnetic material that is less expensive than iron-cobalt alloys and has a higher saturation magnetic flux density Bs than pure iron. 16 N2 is attracting attention. α″-Fe 16 N2 is a body-centered tetragonal (bct) iron-based martensite, and has a crystal structure in which N penetrates α-Fe and the lattice spacing expands in the c-axis direction.
[0004] Iron nitride α″-Fe 16 N2 is a metastable phase, has low thermal stability, and is known to be difficult to grow. 16 Various research and development projects are being conducted on N2, including its manufacturing methods.
[0005] Patent Document 1 describes a magnetic multilayer film in which a film containing a ferromagnetic element and a non-magnetic material having a lattice spacing that matches the lattice spacing of the film containing the ferromagnetic element are alternately epitaxially grown and laminated. The film containing a ferromagnetic element is an Fe-N binary film or an Fe-Co-N ternary film, and is an α″-Fe 16 It uses materials based on N2.
[0006] Patent Document 2 describes a manufacturing method capable of forming an iron nitride film with high saturation magnetism and low coercive force quickly and stably.16 N2 is formed into a laminated structure with α-Fe by reactive sputtering using N2 gas. It is described that the molar ratio of iron to nitrogen changes during nitriding heat treatment. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 6-020834 [Patent Document 1] International Publication No. 1996 / 02925 Summary of the Invention [Problem to be solved by the invention]
[0008] In various applications such as rotating electrical machines and transformers, soft magnetic materials that are inexpensive and have a high saturation magnetic flux density Bs are required. In applications to iron cores, the conversion efficiency between electric energy and magnetic energy is important, and it is desirable to achieve both a high saturation magnetic flux density Bs and low iron loss Pi. Patent documents 1 and 2 disclose α″-Fe alloys that exhibit high Bs but low thermal stability. 16 In order to generate N2, a magnetic film having a laminated structure is formed.
[0009] However, such conventional α″-Fe 16 In N2, a high saturation magnetic flux density Bs comparable to the theoretically calculated value has not been obtained. 16 A high Bs value exceeding the theoretically calculated value of N2 is desired. However, 16 There is no known method to increase the Bs of N2 beyond what is currently available.
[0010] Therefore, the present invention provides iron nitride α″-Fe 16 The object of the present invention is to provide a magnetic material that can provide a saturation magnetic flux density higher than N2, and an iron core and a rotating electric machine using the same. [Means for solving the problem]
[0011] In order to solve the above problems, the magnetic material according to the present invention is a magnetic material containing iron and nitrogen, the magnetic material containing body-centered tetragonal (bct) crystals containing iron and nitrogen, The crystal has nitrogen defects introduced therein, The molar ratio of iron to nitrogen contained in the crystals exceeds 8. The iron core according to the present invention is an iron core in which soft magnetic steel plates are laminated, and part or all of the soft magnetic steel plates are formed from the magnetic material. The rotating electric machine according to the present invention is an iron core in which soft magnetic steel plates are laminated, and part or all of the soft magnetic steel plates are formed from the magnetic material. Effect of the Invention
[0012] According to the present invention, the iron nitride α″-Fe 16 It is possible to provide a magnetic material that can provide a saturation magnetic flux density higher than N2, and an iron core and a rotating electric machine using the same. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram showing the crystal structure of iron nitride α″-Fe16N2. [Diagram 2] FIG. 1 is a diagram showing a crystal structure model in which nitrogen defects are introduced into iron nitride α″-Fe16N2. [Diagram 3] FIG. 13 is a graph showing calculated values of saturation magnetic flux density versus the amount of introduced nitrogen defects. [Figure 4] FIG. 1 is a perspective view illustrating an example of a stator of a rotating electric machine. [Diagram 5] FIG. 2 is an enlarged schematic cross-sectional view of a slot region of the stator. [Figure 6] FIG. 1 is a diagram showing a calculation model used in calculating the electronic structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, a magnetic material according to an embodiment of the present invention, and an iron core and a rotating electric machine using the same will be described with reference to the drawings. In the following drawings, the same reference numerals will be used to designate common configurations, and duplicated descriptions will be omitted.
[0015] <Magnetic material> The magnetic material according to this embodiment is a magnetic material containing iron (Fe) and nitrogen (N), and exhibits ferromagnetism at room temperature. 16 The magnetic material is an iron nitride α″-Fe 2 ferronitride with a bct crystal structure based on N2 and containing iron and nitrogen. 16 The iron nitride has a bct crystal structure with nitrogen defects introduced into it. The nitrogen to iron molar ratio exceeds 8.
[0016] Here, iron nitride α″-Fe 16 The purpose and mechanism of introducing nitrogen vacancies into N2 will be explained.
[0017] Figure 1 shows the iron nitride α″-Fe 16 FIG. 1 shows the crystal structure of N2. Figure 1 shows the iron nitride α″-Fe 16 1 shows a unit cell of N2. In FIG. 1, reference numeral 101 indicates a 4e site occupied by an iron atom. Reference numeral 102 indicates an 8h site occupied by an iron atom. Reference numeral 103 indicates a 4d site occupied by an iron atom. Reference numeral 104 indicates a 2a site occupied by a nitrogen atom.
[0018] As shown in Figure 1, iron nitride α″-Fe 16 The unit cell of N2 contains 16 iron atoms and 2 nitrogen atoms. The iron and nitrogen atoms are regularly arranged. α″-Fe 16 The crystal structure of N2 is body-centered tetragonal (bct) and belongs to the space group I4 / mmm. The experimentally determined literature values indicate that the a-axis lattice constant is 5.72 Å and the c-axis lattice constant is 6.29 Å.
[0019] In the unit cell, the iron atoms occupy three independent crystallographic sites. The iron atoms in the 4e site (101) and the 8h site (102) are bonded to the nitrogen atom in the 2a site (104), whereas the iron atom in the 4d site (103) is not bonded to the nitrogen atom in the 2a site (104). The iron atom in the 4d site (103) is coordinated in a crystal structure similar to that of a body-centered cubic (bcc) crystal.
[0020] Iron nitride α″-Fe 16 N2 is known as a soft magnetic material that exhibits a high saturation magnetic flux density Bs. 16 The reason why N2 shows high Bs has been discussed based on theoretical studies. The magnetic properties of bulk materials are well described by first-principles calculations using density functional theory. 16 The magnetic moment of the iron atom in N2 has been analyzed mainly using first-principles density functional theory.
[0021] Magnetic moment is a vector quantity that describes the magnitude and direction of magnetic force. It is expressed as the vector sum of the intrinsic magnetic moment of the proton, the intrinsic magnetic moment of the electron, and the magnetic moment of the orbital motion of the electron. The magnetic moment of a bulk material is determined primarily by the spin angular momentum of the unpaired electrons. A larger magnetic moment means a stronger magnetic force.
[0022] The first-principles density functional method is a method for approximately calculating various physical properties, including magnetic properties, within the first-principles range using functionals of electron density. The ground state of a system can be obtained by minimizing the energy of the system based on the variational principle. First-principles calculations do not use experimental parameters, so they are highly reliable and can obtain information complementary to experimentally obtained information.
[0023] First-principles density functional calculations show that the iron nitride α″-Fe 16 The average magnetic moment of the iron atoms in N2 is 2.4μ B The average magnetic moment of the iron atom in pure iron is 2.2μ B α″-Fe16 The average magnetic moment of the iron atoms in N2 is about 9% larger than that of pure iron. This difference in magnetic moment is the α″-Fe 16 This gives N2 a high saturation magnetic flux density Bs.
[0024] The inventors have developed iron nitride α″-Fe 16 For N2, the magnetic moment of the iron atoms occupying each crystallographic site was calculated using first-principles density functional theory. The average magnetic moment of the iron atoms is 2.18μ at the 4e site. B , 2.38μ at 8h site B , 2.85μ at 4d site B It was found that the iron atoms in the 4d sites that are not bonded to nitrogen atoms have a specifically higher magnetic moment than the iron atoms that are bonded to nitrogen atoms.
[0025] The magnetic material according to the present embodiment is based on this knowledge, and is made of iron nitride α″-Fe 16 By introducing nitrogen defects into N2 or its heteroelement substitutes, the number of iron atoms not bonded to nitrogen atoms is increased, and the saturation magnetic flux density Bs is improved. Introducing nitrogen defects means making the 2a site of bct an atomic vacancy. Since the introduction of nitrogen defects is expected to increase the number of iron atoms not bonded to nitrogen atoms at the 4e and 8h sites, the magnetic properties were analyzed as follows.
[0026] Figure 2 shows the iron nitride α″-Fe 16 FIG. 1 is a diagram showing a crystal structure model in which nitrogen defects are introduced into N2. In FIG. 2, reference numeral 201 denotes a 4e site occupied by an iron atom. Reference numeral 202 denotes an 8h site occupied by an iron atom. Reference numeral 203 denotes a 4d site occupied by an iron atom. Reference numeral 204 denotes a 2a site occupied by a nitrogen atom. Reference numeral 205 denotes a vacant atomic hole. Reference numeral 206 denotes the boundary of the unit cell of the crystal.
[0027] As shown in Figure 2, iron nitride α″-Fe 16A crystal structure model was created in which nitrogen defects were introduced into N2, and the magnetic moment of the iron atom located at each crystallographic site was calculated using the first-principles density functional method. 16 N 2-x Nine types were analyzed, where x = 0, 0.125, 0.25, 0.5, 0.75, 1.0, 1.25, 1.5, and 1.75. Atomic vacancies (204) were introduced as an ordered array spaced apart from each other.
[0028] FIG. 3 is a graph showing the calculated values of saturation magnetic flux density versus the amount of introduced nitrogen defects. As shown in Figure 3, when no nitrogen vacancies are introduced (x = 0), the average magnetic moment of iron atoms is 2.235 μ B When the amount of nitrogen vacancies introduced into all 2a sites was increased from 0% (x = 0) to 25% (x = 0.5), the average magnetic moment of the iron atoms gradually increased in proportion to the amount of nitrogen vacancies introduced, but the increment was small.
[0029] When the amount of nitrogen vacancies was increased to 25% (x=0.5) or more, the average magnetic moment of the iron atoms increased rapidly in proportion to the amount of nitrogen vacancies. When the amount of nitrogen vacancies was 62.5% (x=1.25), it reached a maximum value of 2.29μ. B When the amount of introduced was 75% (x=1.5), it was 2.27μ. B When the amount introduced is 87.5% (x=1.75), it is 2.256μ B It became about that level.
[0030] From these results, it can be seen that a particularly high average magnetic moment can be obtained by introducing a nitrogen defect amount of 25 to 75 atomic % (0.5≦x≦1.5) relative to the stoichiometric ratio of nitrogen, and that a perfectly crystalline iron nitride α″-Fe 16 It was confirmed that the saturation magnetic flux density Bs can be improved compared to N2. In other words, it was found that the saturation magnetic flux density Bs is improved by making the molar ratio of iron to nitrogen contained in the body-centered tetragonal (bct) crystals exceed 8. It is preferable that the molar ratio of iron to nitrogen contained in the body-centered tetragonal (bct) crystals is 32 or less.
[0031] Conventionally, iron nitride α″-Fe 16 Regarding N2, the reason why the magnetic moment of the iron atom that is not adjacent to the nitrogen atom is high has been explained based on band calculations (Akimasa Sakuma, "Electronic and Magnetic Structures of Nitride Magnetic Materials," Journal of the Japan Institute of Metals (1992), Vol. 31, No. 11, pp. 999-1007).
[0032] According to band calculations, the 3d level of the iron atom bonded to the nitrogen atom shifts to the lower energy side, and the 3d level of the neighboring iron atom shifts to the higher energy side. As a result, electrons flow into the iron atom bonded to the nitrogen atom from the neighboring iron atom, lowering the magnetic moment of the iron atom bonded to the nitrogen atom while raising the magnetic moment of the neighboring iron atom.
[0033] Considering such electron movement, the reason why the magnetic moment increases when nitrogen defects are introduced is believed to be as follows.
[0034] Iron nitride α″-Fe 16 When nitrogen vacancies are introduced into N2, the number of iron atoms bonded to nitrogen atoms decreases. The iron atom adjacent to the 2a site where the nitrogen vacancy is introduced becomes the next nearest neighbor, coordinated to the iron atom adjacent to the nitrogen atom, from the perspective of another iron atom bonded to a nitrogen atom. The next nearest neighbor iron atom is not bonded to a nitrogen atom.
[0035] When no nitrogen vacancies are introduced, the next nearest neighbor site is only the 4d site. However, when nitrogen vacancies are introduced, the 8h site and 4e site also become next nearest neighbor sites. Electrons flow from the iron atom occupying the next nearest neighbor site to the iron atom bonded to the nitrogen atom. As a result, it is thought that the magnetic moment of the next nearest neighbor iron atom becomes higher.
[0036] However, if too many nitrogen vacancies are introduced, the nitrogen in the crystal structure becomes diluted, and many of the sites next to the iron atoms become vacant. If there are too many vacancies, the crystal structure becomes closer to a body-centered cubic (bcc) structure, similar to α-Fe. The average magnetic moment of the iron atoms in α-Fe is 2.2μ B Therefore, iron nitride α″-Fe 16 It is believed that the saturation magnetic flux density Bs does not improve as much as N2.
[0037] Next, a more specific form of a magnetic material containing body-centered tetragonal (bct) crystals containing iron and nitrogen into which nitrogen defects have been introduced will be described.
[0038] A part or all of the iron (Fe) contained in the body-centered tetragonal (bct) crystal with nitrogen defects introduced may be replaced with a metal element such as cobalt (Co), nickel (Ni), etc. Co is preferable as the element to replace Fe because it can obtain a high saturation magnetic flux density Bs.
[0039] From the viewpoint of cost reduction, the Co amount is preferably 25 atomic % or less, and more preferably 20 atomic % or less. When Co is actively added, the Co amount is preferably 1 atomic % or more, and more preferably 5 atomic % or more. When Ni is actively added, the Ni amount is preferably 3 atomic % or less. When Ni is actively added, the Ni amount is preferably 0.01 atomic % or more. The Co amount and Ni amount may be less than the amount equivalent to unavoidable impurities.
[0040] A portion of the nitrogen (N) contained in the body-centered tetragonal (bct) crystals with nitrogen defects introduced may be replaced with light elements such as carbon (C), oxygen (O), and boron (B). The element to replace N is preferably C, since it provides a high magnetic moment. C stabilizes the nonmagnetic gamma phase and produces low-magnetic carbides. However, when an appropriate amount of C is substituted, it is possible to reduce the iron loss Pi while maintaining a high saturation magnetic flux density Bs.
[0041] The content of N is less than 11.1 atomic %. From the perspective of setting the introduction amount of nitrogen defects to 25 - 75% (0.5 ≤ x ≤ 1.5), it is preferably 2.8 atomic % or more and 8.3 atomic % or less. Further, from the perspective of setting the introduction amount of nitrogen defects to 37.5 - 75% (0.75 ≤ x ≤ 1.5), it is preferably 4.2 atomic % or more and 8.3 atomic % or less.
[0042] The content of C is preferably 3 atomic % or less. Also, when C is actively added, the content of C is preferably 0.01 atomic % or more. The content of O is preferably 3 atomic % or less. Also, when C is actively added, the content of O is preferably 0.01 atomic % or more. The content of B is preferably 3 atomic % or less. Also, when B is actively added, the content of B is preferably 0.01 atomic % or more. The contents of C, O, and B may be equal to or less than the equivalent amount of inevitable impurities.
[0043] That is, the magnetic material according to this embodiment includes a body-centered tetragonal (bct) crystal represented by the following general formula (I). Fe 16-a-b Co a Ni b N 2-c-x A c ···(I) [However, in formula (I), M represents one or more elements selected from the group consisting of Co and Ni, A represents one or more elements selected from the group consisting of C, O, and B, and 0 ≤ a < 16, 0 ≤ b < 16, 0 ≤ c < 2, 0 < x < 2 are satisfied.]
[0044] In formula (I), the coefficient x representing nitrogen defects is preferably 0.5 ≤ x ≤ 1.5, more preferably 0.75 ≤ x ≤ 1.5. When Co is actively added, the coefficient a is preferably 0.18 ≤ a ≤ 4.5, more preferably 0.18 ≤ a ≤ 3.6. When Ni is actively added, the coefficient b is preferably 0.18 ≤ b ≤ 0.54. When C, O, or B is actively added, the coefficient c is preferably 0.18 ≤ b ≤ 0.54.
[0045] The lattice constant (c-axis length) of the body-centered tetragonal (bct) c-axis into which nitrogen defects have been introduced is preferably 5.66 Å or more and less than 6.23 Å on average per material. The theoretically calculated c-axis length of bct pure iron is 5.66 Å. Perfectly crystalline α″-Fe 16 The c-axis length of N2 is 6.23 Å. In the above range, nitrogen defects are appropriately introduced, so a high saturation magnetic flux density Bs per volume can be obtained. Note that 1 Å is 0.1 nm.
[0046] The volume of the unit cell of a body-centered tetragonal (bct) crystal with nitrogen vacancies is 181.3 Å on average per material. 3 More than 201.2Å 3 The theoretically calculated volume of the unit cell of bct pure iron is 181.3 Å. 3 Perfectly crystalline α″-Fe 16 The volume of the unit cell of N2 is 201.2 Å. 3 Within the above range, nitrogen defects are appropriately introduced, so that a high saturation magnetic flux density Bs per volume can be obtained.
[0047] The minimum distance between nitrogen atoms in a body-centered tetragonal (bct) crystal with nitrogen defects is preferably 6.8 Å or more. 16 N), the average distance between nitrogen atoms is 6.8 Å. In the above range, nitrogen defects are introduced in a dispersed manner, so that the effect of improving the magnetic moment at the next nearest site of the nitrogen atom can be easily obtained throughout the crystal.
[0048] The volume fraction of body-centered tetragonal (bct) crystals into which nitrogen defects have been introduced is preferably 10% by volume or more, more preferably 30% by volume or more, even more preferably 50% by volume or more, even more preferably 70% by volume or more, and even more preferably 90% by volume or more per 100% by volume of the magnetic material.
[0049] The magnetic material according to this embodiment may partially contain one or more of the α' phase, γ phase, γ' phase, and ε phase of Fe8N, as long as it contains bct containing iron and nitrogen. However, the volume fraction of the non-magnetic γ phase is preferably 5 volume % or less. The volume fraction of the γ' phase, which has a low saturation magnetic flux density Bs, is preferably 5 volume % or less. The volume fraction of the ε phase, which has a low saturation magnetic flux density Bs, is preferably 5 volume % or less.
[0050] In the magnetic material according to this embodiment, the body-centered tetragonal (bct) crystals having nitrogen defects introduced therein may or may not have a concentration gradient for the metal element substituting Fe and the light element substituting N.
[0051] The crystal structure of the magnetic material can be confirmed by X-ray diffraction (XRD) measurement. The chemical composition of the magnetic material can be confirmed by an electron probe micro analyzer (EPMA) or the like. The presence or absence of nitrogen defects can be confirmed by comparing the crystal structure analysis results with the chemical composition analysis results of perfectly crystalline α″-Fe 16 This can be confirmed by comparing with the case of N2. The volume fraction of crystals can be obtained by observing the structure with a scanning electron microscope (SEM) or the like and performing image analysis.
[0052] <Method of manufacturing magnetic materials> The magnetic material according to this embodiment is iron nitride α″-Fe 16 In the synthesis of N2 or its heteroelement-substituted derivatives, the amount of nitrogen can be limited.
[0053] Iron nitride α″-Fe 16Methods for synthesizing N2 or its hetero-element substitutes include a method of subjecting an iron-based material to a nitriding heat treatment, a method of subjecting an iron-based material to a nitriding heat treatment and a denitriding heat treatment, and physical vapor deposition, sputtering, molecular beam epitaxy, ion implantation, etc., in which the amount of nitrogen is limited. Below, the manufacturing methods for magnetic materials will be explained using as examples a method of subjecting an iron-based material to a nitriding heat treatment and a method of subjecting an iron-based material to a nitriding heat treatment and a denitriding heat treatment.
[0054] The magnetic material according to the present embodiment can be obtained by a method that includes a material preparation step, a homogenization heat treatment step, a nitriding heat treatment step, and a cooling step in this order when only the nitriding heat treatment is performed, or by a method that includes a material preparation step, a homogenization heat treatment step, a nitriding heat treatment step, a denitriding heat treatment, and a cooling step in this order when both the nitriding heat treatment and the denitriding heat treatment are performed.
[0055] (Material preparation process) The material preparation step is a step of preparing a starting material for the magnetic material. As the starting material, a plate-shaped, foil-shaped material is prepared. The thickness of the starting material can be, for example, 0.01 mm or more and 1 mm or less. As the starting material, an iron-based material containing a metal element to be substituted for iron or a light element to be substituted for nitrogen can be used. As the iron-based material, pure iron, low-carbon and low-alloy steel, alloy steel, electromagnetic steel, iron-cobalt alloy, etc. can be mentioned.
[0056] The starting material preferably contains 1.5 mass% or less of carbon. The starting material preferably contains 5 mass% or less of alloying elements in total. If the carbon or alloying elements are too much, low magnetic γ phases may remain after martensitic transformation, lowering the saturation magnetic flux density Bs. If the carbon content is too much, carbides that are difficult for nitrogen atoms to dissolve in are formed, preventing the nitrogen atoms from diffusing uniformly.
[0057] (Homogenization heat treatment process) The homogenization heat treatment process is a process in which the starting material is heated to the austenite formation temperature (Ac3 transformation point) or higher to homogenize it. The homogenization heat treatment is carried out in an inert gas atmosphere such as argon gas. For example, the starting material is heated to 900°C or higher to diffuse the chemical components in the material into a highly uniform state.
[0058] (Nitrogen immersion heat treatment process) The nitrous heat treatment process is a process in which a nitrous gas is brought into contact with the material under heat treatment to allow nitrogen to penetrate and diffuse into the material. The nitrous heat treatment is preferably carried out at a temperature higher than the eutectoid temperature (A1 transformation point). This is because nitrogen does not penetrate easily into carbides such as Fe3C, but does form a solid solution in the γ phase and the like. For example, the gas-cooled material is heated to 700 to 900°C, and nitrous gas is supplied under an inert gas atmosphere. Ammonia or the like can be used as the nitrous gas.
[0059] In the nitriding heat treatment process, the amount of nitrogen diffusion can be adjusted in order to introduce nitrogen defects. The nitrogen in the material may or may not form a concentration gradient. When a denitriding heat treatment process is performed, the amount of nitrogen diffusion may not be adjusted in the nitriding heat treatment process, and nitrogen may be diffused in an amount equal to or greater than the stoichiometric ratio.
[0060] The amount of nitrogen diffusion can be adjusted by controlling the amount (partial pressure) of the nitriding gas, the pressure (total pressure) of the atmosphere containing the nitriding gas, the temperature of the nitriding heat treatment, the contact time of the nitriding gas, or a combination of these. The amount of nitrogen defects introduced can be increased by reducing the amount of the nitriding gas, lowering the atmospheric pressure, lowering the temperature, or reducing the contact time of nitrogen.
[0061] (Denitrification heat treatment process) The denitrification heat treatment process is a process in which nitrogen is released from the material under heat treatment to introduce nitrogen defects into the material. The denitrification heat treatment process is carried out when the amount of nitrogen diffusion is not adjusted in the nitriding heat treatment process, and nitrogen is diffused in an amount equal to or greater than the stoichiometric ratio. The denitrification heat treatment can be carried out, for example, by heating the material to 700 to 900°C.
[0062] The amount of nitrogen released can be adjusted by controlling the amount (partial pressure) of nitriding gas, controlling the atmospheric pressure (total pressure), controlling the temperature of denitriding heat treatment, controlling the time of denitriding heat treatment, or a combination of these. The amount of nitrogen released can be increased by controlling to reduce the amount of nitriding gas contacting the material, to lower the atmospheric pressure, to raise the temperature of denitriding heat treatment, or to increase the time of denitriding heat treatment.
[0063] (cooling process) The cooling process is a process in which the material is rapidly cooled to below the martensite transformation temperature (Ms transformation point) to transform into a body-centered tetragonal (bct) martensite structure. Rapid cooling can be performed as a process in which the material is cooled to less than 100°C using coolants such as oil or water, or as a sub-zero process in which the material is cooled to below 0°C using coolants such as dry ice or liquid nitrogen.
[0064] When the material is quenched after the nitrogen immersion heat treatment, a magnetic material with a bct structure in which nitrogen atoms are dissolved in the matrix is obtained. When the amount of nitrogen diffused is reduced in the nitrogen immersion heat treatment process, a magnetic material with nitrogen defects introduced and a molar ratio of iron to nitrogen in the bct crystals exceeding 8 is obtained. The magnetic material may contain a bcc phase in which nitrogen is not dissolved, an austenite phase, an fcc phase of Fe4N, or the like.
[0065] (Carburizing heat treatment process) When replacing a portion of the nitrogen contained in the body-centered tetragonal (bct) crystals into which nitrogen defects have been introduced with carbon, a carburizing heat treatment process can be carried out before or after the nitriding heat treatment process.
[0066] When replacing a part of the nitrogen with carbon, the carburizing treatment can be performed by heat treating the material at a temperature higher than the eutectoid temperature (A1 transformation point) and contacting it with a carbon source. After the material is carburized, it is preferable to cool it to about 200°C to generate carbides. The carburizing treatment can be performed, for example, by gas carburizing. As the carburizing gas, acetylene, methane, propane, butane, etc. can be used. The carburizing gas can be supplied continuously or intermittently under an inert gas atmosphere.
[0067] Next, after the carbides are generated, it is preferable to heat the material to near the eutectoid temperature (A1 transformation point) and hold it there, then rapidly heat it to the austenite formation temperature (Ac3 transformation point) or higher, and then rapidly cool it. For example, the material in which the carbides are generated is heated to 700°C to 900°C and held there, and then rapidly heated to 900°C or higher. The heating rate of the rapid heating is preferably 100°C / sec or higher. The rapid heating is preferably a process of holding the material at around 950°C for about 1 second.
[0068] In this way, when the material is heated to near the eutectoid temperature, the carbides can be dispersed in the α phase, which has a lower solubility limit for carbon than the γ phase. When the material is then rapidly heated, the carbides dispersed in the matrix are rapidly decomposed, allowing the carbon atoms to be dissolved uniformly. Therefore, when the carburizing heat treatment process is followed by the cooling process, a magnetic material is obtained in which some of the nitrogen is replaced by carbon, nitrogen defects are introduced, and the molar ratio of iron to nitrogen in the bct crystal exceeds 8.
[0069] <Soft magnetic steel plate> The magnetic material according to the present embodiment can be used in the form of a plate-shaped or foil-shaped soft magnetic steel sheet. The soft magnetic steel sheet is a steel sheet formed of the magnetic material and exhibits soft magnetism, and contains body-centered tetragonal (bct) crystals containing iron and nitrogen to which nitrogen vacancies have been introduced. As long as the soft magnetic steel sheet contains bct containing iron and nitrogen, it may partially contain one or more of the α' phase, γ phase, γ' phase of Fe8N, and ε phase of Fe3N.
[0070] The soft magnetic steel sheet may contain inevitable impurities in addition to metal elements such as iron (Fe), nitrogen (N), cobalt (Co), and nickel (Ni), and light elements such as carbon (C), oxygen (O), and boron (B). Examples of inevitable impurities include hydrogen (H), silicon (Si), phosphorus (P), sulfur (S), chromium (Cr), manganese (Mn), and copper (Cu). The total content of these elements is preferably 3 atomic % or less.
[0071] The thickness of the soft magnetic steel sheet is, for example, 1 μm or more and 1 mm or less. The soft magnetic steel sheet can be obtained by hot rolling, cold rolling, or a combination of these on a plate-shaped or foil-shaped magnetic material. Annealing can also be performed between the multiple rolling steps within a temperature and time range that does not generate excessive nitrogen defects. The plate-shaped or foil-shaped magnetic material may be subjected to tension annealing treatment, in which annealing is performed while applying tensile stress.
[0072] The soft magnetic steel sheet may be in the form of a laminate of magnetic materials containing body-centered tetragonal (bct) crystals containing iron and nitrogen with a concentration gradient of cobalt formed and nitrogen vacancies introduced therein. The laminated soft magnetic steel sheet may include low carbon steel sheets, electromagnetic pure iron sheets, electromagnetic steel sheets, iron-silicon alloy sheets, iron-cobalt alloy sheets, etc., so long as it contains such magnetic materials.
[0073] <Iron cores / rotating electric machines> The soft magnetic steel plate using the magnetic material according to this embodiment can be used as a material for an iron core. The iron core is formed by punching and laminating a soft magnetic steel plate. Such an iron core can be used in the stator of a rotating electric machine. The iron core may be laminated with a low carbon steel plate, an electromagnetic pure iron plate, an electromagnetic steel plate, an iron-silicon alloy plate, an iron-cobalt alloy plate, or the like, as long as the magnetic material used includes body-centered tetragonal (bct) crystals containing iron and nitrogen-containing nitrogen-containing iron with nitrogen defects.
[0074] Fig. 4 is a perspective view showing a typical example of a stator of a rotating electric machine. Fig. 5 is a cross-sectional view showing an enlarged schematic view of a slot region of the stator. Note that the cross-sectional view means a cross section perpendicular to the direction of the rotation axis (a cross section whose normal line is parallel to the direction of the rotation axis). In the rotating electric machine, a rotor (not shown) is disposed radially inside the stator shown in Figs. 4 and 5.
[0075] As shown in Figures 4 and 5, stator 10 has stator coils 20 wound in a plurality of stator slots 12 formed on the inner periphery of iron core 11. Stator slots 12 are spaces that are arranged in a predetermined circumferential pitch around the circumferential direction of iron core 11 and penetrate in the axial direction, with slits 13 opening in the innermost periphery and extending in the axial direction. Areas separating adjacent stator slots 12 are referred to as teeth 14 of iron core 11. Portions of inner periphery tip areas that define slits 13 are referred to as tooth claw portions 15.
[0076] The stator coil 20 is usually composed of a plurality of segment conductors 21. For example, in Fig. 4 and Fig. 5, the stator coil 20 is composed of three segment conductors 21 corresponding to the U-phase, V-phase, and W-phase of a three-phase AC. In order to prevent partial discharge between the segment conductors 21 and the iron core 11 and partial discharge between the phases (U-phase, V-phase, W-phase), the outer periphery of each segment conductor 21 is usually covered with an electrical insulating material 22 (e.g., insulating paper or enamel coating).
[0077] The iron core and rotating electric machine using the soft magnetic steel sheet according to this embodiment are an iron core 11 formed by laminating multiple soft magnetic steel sheets according to this embodiment in a predetermined shape in the axial direction, and a rotating electric machine using the iron core 11. Since soft magnetic steel sheets exhibit magnetic properties of a saturation magnetic flux density Bs exceeding that of pure iron and a coercive force Hc equal to or less than that of pure iron, it is possible to provide an iron core with higher conversion efficiency between electric energy and magnetic energy than an iron core using a conventional electromagnetic steel sheet. A highly efficient iron core can realize a smaller rotating electric machine and higher torque.
[0078] In addition, the soft magnetic steel plate according to this embodiment can be made of low-carbon steel plate, electromagnetic pure iron plate, etc., which have lower material costs than Fe-Co steel plate, and therefore has the advantage of being able to provide highly efficient iron cores and rotating electric machines at low cost.
[0079] A rotating electric machine using the soft magnetic steel sheet according to this embodiment in its iron core includes such a stator (core) 10, a stator coil 20, and a rotor. When a magnetic material containing body-centered tetragonal (bct) crystals containing iron with nitrogen defects and nitrogen is used as the material for the teeth 14, tooth claw portions 15, and back yoke of the iron core 11, the soft magnetic steel sheet according to this embodiment has a magnetic property similar to that of a conventional perfect crystal α″-Fe 16 Compared to the case where N2 is used, a high saturation magnetic flux density Bs can be obtained.
[0080] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, the present invention is not necessarily limited to having all the configurations of the above embodiment. It is possible to replace a part of the configuration of an embodiment with another configuration, add a part of the configuration of an embodiment to another form, or omit a part of the configuration of an embodiment. EXAMPLES
[0081] The present invention will be described in more detail below with reference to various examples, although the present invention is not limited to the configurations and structures of these examples.
[0082] [Analysis 1] α″-Fe 16 A computational model was constructed in which one nitrogen atom was removed from the unit cell of N2, and its electronic structure was determined using the first-principles density functional method, and the magnetic moment, lattice constant, unit cell volume, and saturation magnetic flux density Bs were calculated.
[0083] The generalized gradient approximation (GGA) was used as the exchange-correlation functional. The cutoff energy in the plane wave expansion of the wave function was set to 500 eV. The integration points in the Brillouin zone were divided into four along each axis, for a total of 64 points. This condition allows the energy to be evaluated with sufficient accuracy.
[0084] FIG. 6 is a diagram showing a calculation model used in calculating the electronic structure. Figure 6 shows a calculation model of a body-centered tetragonal (bct) crystal used in the calculation of the electronic structure. In Figure 6, reference numeral 601 indicates an atomic vacancy at the 2a site introduced as a nitrogen defect. Reference numeral 602 indicates a 4e site. Reference numeral 603 indicates an 8h site. Reference numeral 604 indicates a site.
[0085] As shown in Figure 6, Fe 16 The nitrogen atom located at the center of the unit cell of N2 was removed to form an atomic vacancy 601. The introduction of a nitrogen defect changes the stable position of the iron atom that was bonded to the nitrogen atom. The stable position of each atom after the introduction of the nitrogen defect was determined based on energetic stability by calculating the force acting on each atom and successively updating the atomic coordinates. While updating the atomic coordinates, the lattice shape of the unit cell was also optimized until the force acting between each atom became zero.
[0086] Nitrogen vacancy-introduced Fe 16 The calculation of the electronic structure of N showed that the magnetic moment of the iron atom at the 4e site (602), which is no longer bonded to the nitrogen atom, is 2.51μ B When no nitrogen vacancies were introduced, the B Therefore, 0.33μ B The introduction of nitrogen defects increased the magnetic moment by 15%, which supports the idea of the present inventors.
[0087] In addition, the magnetic moment of the iron atom at the 8h site (603), which is no longer bonded to the nitrogen atom, is 2.46μ B When no nitrogen vacancies were introduced, theB Therefore, 0.08μ B The introduction of nitrogen vacancies increases the magnetic moment by 3%, and although the effect is smaller than that of the 4e site (602), the effect of improving the saturation magnetic flux density Bs was confirmed.
[0088] On the other hand, the magnetic moment of the iron atom in the 4d site (604) that is not bonded to a nitrogen atom is 2.67μ B When no nitrogen vacancies were introduced, the B Therefore, 0.18μ B The introduction of nitrogen vacancies resulted in a 6% decrease in the magnetic moment.
[0089] Nitrogen vacancy-introduced Fe 16 The total magnetic moment in the unit cell of N is 37.9μ B When no nitrogen vacancies were introduced, the B Therefore, 0.7μ B This means that the magnetic moment of the unit cell has decreased. However, from the viewpoint of practical use of magnetic materials, the saturation magnetic flux density Bs is more important than the magnetic moment of the unit cell. The magnetic flux per unit cell volume can be calculated by dividing the magnetic moment of the unit cell by the volume of the unit cell.
[0090] Fe with no nitrogen vacancies 16 The volume of the unit cell of N2 is 201.2 Å. 3 It was. 16 The saturation magnetic flux density Bs per unit cell volume of N2 was 2.23 T. On the other hand, the Fe 16 The volume of the unit cell of N is 193.3 Å. 3 It was. 16 The saturation magnetic flux density Bs per volume of the N unit cell was 2.28T.
[0091] As shown above, when nitrogen vacancies were introduced, the magnetic moments of the 4e and 8h sites increased as expected, while the magnetic moment of the 4d site decreased. It was found that the introduction of nitrogen vacancies decreased the magnetic moment of the unit cell, but the volume of the unit cell became smaller, resulting in a higher magnetic flux density per unit cell volume and a high saturation magnetic flux density Bs.
[0092] [Analysis 2] Co 16 A computational model was constructed in which one nitrogen atom was removed from the unit cell of N2, and its electronic structure was determined by first-principles calculations using density functional theory, and the magnetic moment, unit cell volume, and saturation magnetic flux density Bs were calculated.
[0093] Analysis 2: Fe 16 The purpose of the analysis is to confirm that the effect of introducing nitrogen defects can be obtained even if the iron atom of N2 is replaced by another element. The calculation of analysis 2 was performed in the same manner as analysis 1, by calculating the forces acting on each atom under the bct structure to derive the equilibrium state, and the atomic coordinates and lattice shape in the equilibrium state were calculated. 16 A similar calculation was performed for N2.
[0094] Co without nitrogen vacancies 16 The total magnetic moment in the unit cell of N2 is 23.0μ B As expected, Co has a smaller magnetic moment than iron. 16 The total magnetic moment in the unit cell of N2 is Fe 16 It is smaller than the total magnetic moment in the unit cell of N2.
[0095] On the other hand, nitrogen vacancies were introduced into Co 16 The total magnetic moment in the unit cell of N is 24.4μ B When no nitrogen vacancies were introduced, the B Therefore, 1.4μ B This means that a magnetic moment of
[0096] Co without nitrogen vacancies 16 The volume of the unit cell of N2 is 187.1 Å. 3 It was. 16 The saturation magnetic flux density Bs per unit cell volume of N2 was 1.43 T. On the other hand, 16 The volume of the unit cell of N is 180.9 Å. 3 It was. 16 The saturation magnetic flux density Bs per volume of the N unit cell was 1.57T.
[0097] As described above, when nitrogen vacancies are introduced, the volume of the unit cell becomes 6.2Å. 3 The decrease in the nitrogen vacancy-introduced Co was 3% smaller than that without the nitrogen vacancy. 16 In the case of N, a high saturation magnetic flux density Bs was obtained. 16 It was confirmed that the effect of introducing nitrogen vacancies can be obtained even when the iron atom of N2 is replaced with another element.
[0098] [Analysis 3] Fe 16 A computational model was constructed in which one carbon atom was removed from the unit cell of C2, and its electronic structure was determined by first-principles calculations using density functional theory, and the magnetic moment, unit cell volume, and saturation magnetic flux density Bs were calculated.
[0099] Analysis 3: Fe 16 The purpose of this study is to confirm that the effect of introducing light element defects can be obtained even if the nitrogen atoms of N2 are replaced by other elements. The calculations in Analysis 3 were performed in the same manner as in Analysis 2, by calculating the forces acting on each atom in the bct structure to derive the equilibrium state, and the atomic coordinates and lattice shape in the equilibrium state were determined. Note that for perfect crystal Fe with no light element defects introduced, 16 The same calculation was performed for C2.
[0100] Fe without light element defects 16 The total magnetic moment in the C2 unit cell is 36.9μ B It was. 16 In N2, 38.6μB Therefore, 1.7μ B This means that the magnetic moment of
[0101] Fe with light element defects 16 The total magnetic moment in the unit cell of C is 37.5μ B When no light element defects were introduced, the B Therefore, 0.6μ B This means that a magnetic moment of
[0102] Fe without light element defects 16 The volume of the unit cell of C2 is 200.3 Å. 3 It was. 16 The saturation magnetic flux density Bs per unit cell volume of C2 was 2.15 T. On the other hand, Fe 16 The volume of the unit cell of C is 193.1 Å 3 It was. 16 The saturation magnetic flux density Bs per volume of the unit cell of C was 2.26T.
[0103] As described above, even when light element defects were introduced, a high saturation magnetic flux density Bs was obtained compared to the case of a perfect crystal. 16 It was confirmed that the effect of introducing light element defects can be obtained even when the nitrogen atoms of N2 are replaced by other light elements.
[0104] Table 1 shows the magnetic moment, lattice constant, unit cell volume, and saturation magnetic flux density Bs. 16 N 2-x The lattice constants are expressed as follows: x = 0, 0.25, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, 2.0.
[0105] [Table 1]
[0106] As shown in Analyses 1 to 3, α″-Fe 16It was confirmed that the introduction of nitrogen defects into N2 causes a change in the magnetic moment or the volume of the crystal, resulting in an improvement in the saturation magnetic flux density Bs per unit cell volume. By including a bct crystal structure with such nitrogen defects in a magnetic material, the α″-Fe 16 It can be said that a higher saturation magnetic flux density Bs can be obtained compared to the case of N2. [Explanation of symbols]
[0107] 10... stator, 11... iron core, 12... stator slot, 13... slit, 14... teeth, 15... teeth claw portion, 20... stator coil, 21... segment conductor, 22... electrical insulation material, 101... iron (4e site), 102... iron (8h site), 103... iron (4d site), 104... nitrogen (2a site), 201... iron (4e site), 202... iron (8h site), 203... iron (4d site), 204... nitrogen (2a site), 205... atomic vacancy, 206... crystal unit cell boundary
Claims
1. A magnetic material containing iron and nitrogen, the magnetic material comprising body-centered tetragonal (bct) crystals containing iron and nitrogen, the crystals having nitrogen defects introduced therein, and a molar ratio of iron to nitrogen contained in the crystals exceeding 8.
2. The magnetic material according to claim 1 , A magnetic material in which the molar ratio of iron to nitrogen contained in the crystal is 32 or less.
3. The magnetic material according to claim 1 , A magnetic material in which part or all of the iron contained in the crystals is replaced with cobalt.
4. The magnetic material according to claim 1 , A magnetic material in which some of the nitrogen contained in the crystals is replaced with carbon.
5. The magnetic material according to any one of claims 1 to 4, A magnetic material in which the lattice constant of the c-axis of the crystal is less than 6.23 Å.
6. The magnetic material according to any one of claims 1 to 4, The volume of the unit cell of the crystal is 201.2 Å 3 Magnetic materials that are less than
7. The magnetic material according to any one of claims 1 to 4, A magnetic material in which the shortest distance between nitrogen atoms contained in the crystal is 6.8 Å or more.
8. The magnetic material according to claim 1 , A magnetic material having an amount of nitrogen of 2.8 atomic % or more and 8.3 atomic % or less.
9. The magnetic material according to claim 1 , A magnetic material having a cobalt content of 25 atomic percent or less.
10. 5. An iron core in which soft magnetic steel plates are laminated, the soft magnetic steel plates being partly or entirely formed of the magnetic material according to claim 1.
11. 5. A rotating electric machine having an iron core in which soft magnetic steel plates are laminated, the soft magnetic steel plates being formed in part or in whole from the magnetic material according to claim 1.
Citation Information
Patent Citations
Manufacture of soft magnetic powder
JP1993074620A
Magnetic multilayer film
JP1994020834A
Soft magnetic composite material and manufacturing method therefor
JP2019143238A
Magnetic thin film and production method therefor
WO1996002925A1